Self-assembly of soybean peroxidase nanohybrid for activity enhancement and dye decolorization: experimental and computational studies. Issue 23 (19th December 2022) - Bhapkar, Sunil; Kumbhar, Navanath; Sharma, Praful; Jagtap, Shweta; Gacche, Rajesh; Barvkar, Vitthal T.; Sonune, Dnyaneshwar; Sonawane, Kailas D.; Jadhav, Umesh
Abstract: The soybean peroxidase (SBP) mediated nanohybrid [SBP-Cu3 (PO4 )2 ·3H2 O] synthesis was carried out in the present study. The scanning electron microscopy (SEM) analysis showed a characteristic flower-like hierarchical structure of the SBP-nanohybrid. The mechanism of SBP-nanohybrid formation was elucidated using computational approaches. The predicted Cu 2+ binding sites followed by molecular docking studies showed the two lowest energy (−4.4 kcal/mol and −3.56 kcal/mol) Cu 2+ binding sites. These two binding sites are located at the opposite position and might be involved in the formation of SBP-nanohybrid assemblies. Further, these sites are different than the catalytic active site pocket of SBP, and may facilitate more substrate catalysis. Obtained computational results were confirmed by in-vitro guaiacol oxidations studies using SBP-nanohybrid. The effect of various parameters on SBP-nanohybrid activity was studied. The pH 7.2 was found optimum for SBP-nanohybrid activity. The enzyme activity increased with an increase in temperature up to 50 °C temperature and then decreased with an increase in temperature. Around ∼138% enhanced activity was recorded using SBP-nanohybrid compared to crude SBP. Also, the SBP-nanohybrid showed around 95% decolorization of methylene blue (MB) in 1 h and the MB degradation was confirmed by high-pressure liquid chromatography analysis (HPLC). Communicated by Ramaswamy H. Sarma